2016
DOI: 10.1099/jmmcr.0.005076
|View full text |Cite
|
Sign up to set email alerts
|

Acute influenza virus-associated encephalitis and encephalopathy in adults: a challenging diagnosis

Abstract: Background: Acute influenza-associated encephalopathy/encephalitis (IAE) in adults is a rare but well-known complication of influenza virus infection. The diagnosis is difficult to make due to the absence of distinctive clinical symptoms and validated diagnostic criteria. We present an illustrative case and a case review on acute IAE in adults.Methods: We performed a Medline search of the English literature using the terms influenz*, encephal* and adult, and constructed a database of detailed descriptions of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 52 publications
(90 reference statements)
3
40
1
4
Order By: Relevance
“…CSF samples in previous case reports were negative for influenza B virus, as in our patient. Meijer et al reported that influenza virus RNA in CSF was detected in 16% of cases, which may be explained by viral CSF concentrations of influenza virus being too low for detection by regular diagnostic tests 10. Otherwise, CSF may reveal lymphocytosis or raised protein, which was similar to our patient.…”
Section: Discussionsupporting
confidence: 76%
“…CSF samples in previous case reports were negative for influenza B virus, as in our patient. Meijer et al reported that influenza virus RNA in CSF was detected in 16% of cases, which may be explained by viral CSF concentrations of influenza virus being too low for detection by regular diagnostic tests 10. Otherwise, CSF may reveal lymphocytosis or raised protein, which was similar to our patient.…”
Section: Discussionsupporting
confidence: 76%
“…Her normal magnetic resonance imaging (MRI) and her subsequent full recovery are consistent with the prior finding, in adult patients, that a normal MRI is of prognostic value [3]. …”
Section: Case Presentationsupporting
confidence: 79%
“…Influenza is difficult to detect on cerebral spinal fluid PCRs and is only positive in approximately 16% of patients [3]. After excluding immediate life threats with a typical AMS evaluation (including CT/LP, toxicologic studies, evaluation for trauma), additional diagnostic testing for flu encephalopathy typically includes an MRI/MRA and EEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oseltamivir treatment for influenza is associated with significant decrease in the risk of recurrent cardiovascular events in subjects with a history of cardiovascular disease (Casscells et al, 2009). Neurological complications of influenza include febrile convulsion, encephalitis, encephalopathy and Guillain Barre Syndrome (Meijer et al, 2016;Tomas et al, 2015). Influenza associated encephalitis is more common in pediatric patients but has been reported in 4% of hospitalized adults, with a mortality rate of 21% while 25% of patients may have residual neurological deficits (Sellers et al, 2017).…”
Section: Under-recognized and Unusual Presentations Of Influenzamentioning
confidence: 99%